2018
DOI: 10.1371/journal.pone.0190113
|View full text |Cite
|
Sign up to set email alerts
|

Cost and affordability of non-communicable disease screening, diagnosis and treatment in Kenya: Patient payments in the private and public sectors

Abstract: IntroductionThe prevalence of non-communicable diseases (NCDs) is rising in low- and middle-income countries, including Kenya, disproportionately to the rest of the world. Our objective was to quantify patient payments to obtain NCD screening, diagnosis, and treatment services in the public and private sector in Kenya and evaluate patients’ ability to pay for the services.Methods and findingsWe collected payment data on cardiovascular diseases, diabetes, breast and cervical cancer, and respiratory diseases fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 16 publications
(16 reference statements)
4
107
1
Order By: Relevance
“…Financing of interventions for the early detection of breast cancer is justified from a public health, economic, and equity perspective. Numerous studies have documented the catastrophic health expenditures and economic hardships associated with a late‐stage diagnosis in patients with breast cancer in different world regions, regardless of resource level 55‐57 . There also are considerable nonmedical costs (transport, lodging, child care), which can account for up to 50% of total costs and must be taken into consideration to reduce the risk of impoverishment 55…”
Section: Situational Analysismentioning
confidence: 99%
“…Financing of interventions for the early detection of breast cancer is justified from a public health, economic, and equity perspective. Numerous studies have documented the catastrophic health expenditures and economic hardships associated with a late‐stage diagnosis in patients with breast cancer in different world regions, regardless of resource level 55‐57 . There also are considerable nonmedical costs (transport, lodging, child care), which can account for up to 50% of total costs and must be taken into consideration to reduce the risk of impoverishment 55…”
Section: Situational Analysismentioning
confidence: 99%
“…In addition, it has been shown that households with a member with an NCD are two times more likely to incur catastrophic health expenditure compared with households where no member has an NCD . A minority of individuals (19%) in Kenya have health insurance coverage, and almost all employees in the formal sector, which is less than one‐fifth of those employed, are covered through the National Hospital Insurance Fund (NHIF) …”
Section: Introductionmentioning
confidence: 99%
“…16 A minority of individuals (19%) in Kenya have health insurance coverage, 17 and almost all employees in the formal sector, which is less than one-fifth of those employed, are covered through the National Hospital Insurance Fund (NHIF). 18,19 Several studies done in Kenya have identified a high prevalence of hypertension (ranging from 12.3% to 50.1%). 6,20,21 Examining the costs incurred by patients to access hypertension care is necessary as evidence suggests they are a barrier to access.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient infrastructure, geographic location, limited workforce capacity, and chronic underfunding can result in health systems that are ill‐equipped to manage the epidemiologic transition from communicable to noncommunicable diseases. This is compounded by financial barriers to access, including a lack of health insurance and high out‐of‐pocket payments and indirect costs 14‐18 . Unfavorable outcomes also are influenced by sociocultural factors, such as stigma, myths, language barriers, gender norms, discrimination, social class, and health literacy 11,15,16,19 .…”
Section: Introductionmentioning
confidence: 99%